2022
DOI: 10.14202/vetworld.2022.147-161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trimmed asparagus by-products supplementation in broiler diets on performance, nutrients digestibility, gut ecology, and functional meat production

Abstract: Background and Aim: Trimmed asparagus by-products (TABP) is the resultant waste from asparagus possessing. TABP has fructans, such as inulins and fructooligosaccharide, which can be utilized as an alternative prebiotic. This study was conducted to examine the effect of TABP dietary supplementation on the productive performance, nutrient digestibility, gut microbiota, volatile fatty acid (VFA) content, small-intestine histology, and meat quality of broilers. Materials and Methods: A total of 320 1-day-old broi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…In addition to improving production efficiency, it is expected that such additives can improve meat quality and animal immunity, among other things. One of the side streams that has been successfully applied to improve livestock immunity was the asparagus by-product [139]. In these studies, the cytoprotective effect on the intestinal epithelial cells and a beneficial effect on the intestinal microbiota profile of broiler chicks were reported after the diet supplementation with trimmed asparagus byproducts.…”
Section: Impact On Various Aspects Of Livestock Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to improving production efficiency, it is expected that such additives can improve meat quality and animal immunity, among other things. One of the side streams that has been successfully applied to improve livestock immunity was the asparagus by-product [139]. In these studies, the cytoprotective effect on the intestinal epithelial cells and a beneficial effect on the intestinal microbiota profile of broiler chicks were reported after the diet supplementation with trimmed asparagus byproducts.…”
Section: Impact On Various Aspects Of Livestock Immunitymentioning
confidence: 99%
“…In these studies, the cytoprotective effect on the intestinal epithelial cells and a beneficial effect on the intestinal microbiota profile of broiler chicks were reported after the diet supplementation with trimmed asparagus byproducts. Nopparatmaitree et al [139] reported that 10-50 g/kg supplementation of broiler chicks (Ross 308 ® ) with trimmed asparagus by-products significantly increased LAB and Enterococcus spp. quantity, as well as acetic, propionic, butyric, and total SCFA levels.…”
Section: Impact On Various Aspects Of Livestock Immunitymentioning
confidence: 99%
“…Besides containing nutrients as conventional feedstuffs, functional feed contains various bioactive compounds that can have promoting impacts on the health and growth of broilers (Sugiharto et al., 2018 ). Moreover, functional feed could improve the carcass traits (Alwaleed et al., 2020 ) and meat quality of broilers (Nopparatmaitree et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%